ANALISIS DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PABRIK GULA PTPN XIVKABUPATEN TAKALAR - Arfiany Arfiany (Jurnal Bisnis dan Kewirausahaan, 2016)
The aim of this study was to determine how much influence the discipline of working on the performance of employees at the sugar factory PTPN XIV Takalar. The study population was all the employees of the sugar factory PTPN XIV Takalar which amounted to 60 employees. While the sampling method used is a method of sampling is saturated, so the sample size is determined as many as 60 people. To obtain the required data, then the data collection methods used were observation and interview. While the method of analysis used is descriptive analysis, simple regression analysis, coefficient of determination, correlation analysis and hypothesis testing. Based on the analysis of research on the effect of labor discipline on the performance of employees in the sugar factory PTPN XIV Takalar, it can be concluded that there is significant influence between disciplines working with employee performance.